Clinical outcomes and genotype-phenotype correlations in patients with complete and partial androgen insensitivity syndromes - Nae-yun Lee; Ja Hye Kim; Ji-Hee Yoon; Soojin Hwang; Gu-Hwan Kim; Han-Wook Yoo; Jin-Ho Choi (Korean Society of Pediatric Endocrinology, 2023)
Purpose Androgen insensitivity syndrome (AIS) is a rare X-linked recessive disorder caused by unresponsiveness to androgens because of mutations in the AR gene. Here, we investigated the clinical outcomes and molecular spectrum of AR variants in patients with AIS attending a single academic center. Methods This study included 19 patients with AIS who were confirmed by molecular analysis of AR. Clinical features and endocrinological findings were retrospectively collected, including presenting features, external genitalia, sex of rearing, timing of gonadectomy, pubertal outcomes, and sex hormone levels. Molecular analysis of AR was performed using Sanger, targeted gene panel, or whole-exome sequencing. Results Among all 19 patients, 14 (74%) were classified as having complete AIS (CAIS), whereas 5 (26%) had partial AIS (PAIS). All patients with CAIS, and 3 patients with PAIS were reared as female. One patient with CAIS manifested a mixed germ cell tumor at the age of 30 years. Molecular analysis of AR identified 19 sequence variants; 12 (63%) were previously reported, and the remaining 7 (37%) were novel. Missense mutations were the most common type (12 of 19, 63%), followed by small deletions, nonsense mutations, an insertion, and a splice site mutation. Conclusions Here, we describe the clinical outcomes and molecular characteristics of 19 Korean patients with AIS. Patients with PAIS manifested various degrees of masculinization of the external genitalia. Nonsense and frameshift mutations were frequent in patients with CAIS, whereas patients with PAIS harbored exclusively missense mutations.